The alternative Augustan age - Morrell, Kit; Osgood, Josiah; Welch, Kathryn (Oxford scholarship online, 2019)
This text boldly reinterprets the central period of Roman history by taking the focus off the emperor Augustus. Its chapters highlight the contributions of other individuals and continuities with republican culture. Together they show that Augustus has been more dominant in later memory than he was in his own lifetime.